Chemotherapy after PD‐1 inhibitors in relapsed/refractory Hodgkin lymphoma: Outcomes and clonal evolution dynamics. (25th April 2022) - Calabretta, Eleonora; Guidetti, Anna; Ricci, Francesca; Di Trani, Martina; Monfrini, Chiara; Magagnoli, Massimo; Bramanti, Stefania; Maspero, Davide; Morello, Lucia; Merli, Michele; Di Rocco, Alice; Graudenzi, Alex; et al.
Summary: Checkpoint inhibitors (CPIs) are routinely employed in relapsed/refractory classical Hodgkin lymphoma. Nonetheless, persistent long‐term responses are uncommon, and one‐third of patients are refractory. Several reports have suggested that treatment with CPIs may re‐sensitize patients to chemotherapy, however there is no consensus on the optimal chemotherapy regimen and subsequent consolidation strategy. In this retrospective study we analysed the response to rechallenge with chemotherapy after CPI failure. Furthermore, we exploratively characterized the clonal evolution profile of a small sample of patients ( n = 5) by employing the CALDER approach. Among the 28 patients included in the study, 17 (71%) were primary refractory and 26 (92%) were refractory to the last chemotherapy prior to CPIs. Following rechallenge with chemotherapy, response was recorded in 23 (82%) patients experiencing complete remission and 3 (11%) patients experiencing partial remission. The tumour evolution of the patients inferred by CALDER seemingly occurred prior to the first cycle of therapy and was characterized either by linear or branching evolution patterns. Twenty‐five patients proceeded to allogeneic stem cell transplantation. At a median follow‐up of 21 months, median PFS and OS were not reached. In conclusion, patients who fail CPIs can be effectively rescued by salvage chemotherapy and bridged to allo‐SCT/auto‐SCT.